2013
DOI: 10.1007/978-3-319-00395-5_56
|View full text |Cite
|
Sign up to set email alerts
|

Topology Drives Calcium Wave Propagation in 3D Astrocyte Networks

Abstract: Glial cells are non-neuronal cells that constitute the majority of cells in the human brain and significantly modulate information processing via permanent cross-talk with the neurons. Astrocytes are also themselves inter-connected as networks and communicate via chemical wave propagation. How astrocyte wave propagation depends on the local properties of the astrocyte networks is however unknown. In the present work, we investigate the influence of the characteristics of the network topology on wave propagatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Astrocytes in vivo exist within a 3D matrix compared to in vitro astrocytes, which grow on a flat surface that restricts diffusion of extracellular signals and gap-junction connections to cells within a 2D plane. Lallouette et al demonstrated in computational models of astrocytic Ca 2+ signalling that different types of intercellular Ca 2+ signalling, specifically regenerative long-range Ca 2+ waves and localised synchrony of Ca 2+ transients, could be replicated simply by changing the structure of the connections between cells [37].…”
Section: Ca 2+ Signalling In Patterned Culturesmentioning
confidence: 99%
“…Astrocytes in vivo exist within a 3D matrix compared to in vitro astrocytes, which grow on a flat surface that restricts diffusion of extracellular signals and gap-junction connections to cells within a 2D plane. Lallouette et al demonstrated in computational models of astrocytic Ca 2+ signalling that different types of intercellular Ca 2+ signalling, specifically regenerative long-range Ca 2+ waves and localised synchrony of Ca 2+ transients, could be replicated simply by changing the structure of the connections between cells [37].…”
Section: Ca 2+ Signalling In Patterned Culturesmentioning
confidence: 99%
“…In the case of Figure 2E, for example, stimulated FM-encoding cells could trigger Ca 2+ signaling in neighboring cells in a regenerative fashion thus extending their tuned response in space. On the other hand, AFM cells, acting as propagation barriers, could shape the borders of this tuned response, eventually drawing the topographical features of the ensuing functional map (Lallouette and Berry, 2012). …”
Section: Computational Aspects Of Propagating Ca2+ Signalsmentioning
confidence: 99%
“…The involvement of astrocyte in the columnar model is considered in [96]. Apart from astrocyte-neuron network, [98] studies the astrocyte wave propagation process by varying the topology of the astrocyte network. Astrocytes occupy spatial territories and connect to their neighbors without overlap.…”
Section: Astrocytic Modelmentioning
confidence: 99%